The cake problem : equivalent and simplified fractions - Wise, Bill, 1958- (Wise, Bill, 1958- Hilariously simple math., 2025)
"Farmer Ed brings Sheep, Chicken, and Goat a chocolate cake. Delicious! But hold on, it's not a circle or rectangle, like most cakes. Dividing this cake is going to be tricky. Luckily, Goat has the solution. If the cake is cut in half, Goat gets one half and Sheep and Chicken share the other half. Easy peasy, milk and cheesy! Or is there a better way?" --Provided by publisher.